2011
DOI: 10.1352/1934-9556-49.4.233
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With the Early Work Experiences of Adolescents With Severe Disabilities

Abstract: The early work experiences of a nationally representative sample of youth with severe disabilities (i.e., intellectual disabilities, autism, multiple disabilities) were examined. Using data from the National Longitudinal Transition Study-2, we explored the extent to which various student-, family-, school-, and community-level factors were associated with paid work experiences during high school. Findings highlight the elusiveness of early work experiences for many youth with severe disabilities and call atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(94 citation statements)
references
References 28 publications
3
83
2
6
Order By: Relevance
“…For example, Carter, Austin, and Trainor (2011) found that fewer than 30% of youth with severe disabilities reported a paid-work experience during school in a study of factors associated with paid-work experience during high school. Similarly, a NLTS-2 Report indicated that only 19% of a nationally representative sample of youth with disabilities participated in paid-work experience during school.…”
Section: Research-article2013mentioning
confidence: 99%
“…For example, Carter, Austin, and Trainor (2011) found that fewer than 30% of youth with severe disabilities reported a paid-work experience during school in a study of factors associated with paid-work experience during high school. Similarly, a NLTS-2 Report indicated that only 19% of a nationally representative sample of youth with disabilities participated in paid-work experience during school.…”
Section: Research-article2013mentioning
confidence: 99%
“…More than almost any other factor, expectations shape outcomes (Carter, Austin, & Trainor, 2011;Doren, Grau, & Lindstrom, 2012). Nationally, high school students with severe disabilities whose parents expected them to work were 5 times as likely to have paid, community employment in the early years after graduation (Carter, Austin, & Trainor, 2012).…”
Section: Elevating Expectationsmentioning
confidence: 99%
“…Ils doivent être encouragés à communiquer de grandes attentes à leur enfant, à lui donner des responsabilités à la maison et à faciliter l'exercice de responsabilités dans sa communauté (Carter et al, 2011;Mill et al, 2009). Le rôle de premier plan exercé par le milieu familial lors de la transition est souligné dans une étude québécoise récente, qui décrit six facteurs de protection mis en place par les parents pour faciliter l'accès à une vie active à leur enfant ayant une déficience intellectuelle, après la fin de la scolarisation .…”
Section: Des Jeunes Et Des Familles Mieux Informésunclassified
“…L'effet positif des expériences de travail commençant tôt, pendant que la personne est encore aux études, a été documenté dans plusieurs recherches (Carter et al, 2011;Hetherington et al, 2010;Johnson, 2004;Landmark et al, 2010;Morningstar & Liss, 2008;Timmons et al, 2011;Winn & Hay, 2009). …”
Section: La Participation Sociale Et Professionnelle L'engagement Counclassified
See 1 more Smart Citation